The influence of first ray instability and hindfoot valgus in the development of hallux rigidus: state of art - Colò, Gabriele; Fusini, Federico; Zoccola, Kristijan; Samaila, Elena Manuela; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2023)
Hallux rigidus (HR) is a painful condition associated with degenerative arthritis of the first metatarsophalangeal (MTP1) joint, leading to a progressive loss of dorsiflexion. The etiological factors leading to the development of the condition are not yet fully understood in the literature. When the hindfoot is aligned in excessive valgus, the medial border of the foot tends to roll over, which brings to increased stress on the medial side of the MTP1 joint, and consequently on the first ray (FR), thus potentially influencing the development of HR deformity. This state of art aims to analyze the influence of FR instability and hindfoot valgus in HR development. From the results of the analyzed studies, it appears that a FR instability may predispose the big toe to increased stress and to narrow the proximal phalanx motion on the first metatarsal, which brings to compression and ultimately degeneration of the MTP1 joint, mostly in advanced stages of disease, less in mild or moderate HR patients.A strong correlation between a pronated foot and MTP1 joint pain was found; forefoot hypermobility during the propulsion phase may promote MTP1 joint instability and increase pain.Thus, the increased moment of pronation of the foot with the overload of the medial column, when present, should be corrected conservatively or surgically; this, most likely, would be useful not only to eliminate or at least limit the painful symptoms but above all to prevent the worsening of the condition, also after the surgical treatment of HR.